2019
DOI: 10.3389/fmicb.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions Improved Rumen Functions and Promoted Compensatory Growth of Growth-Retarded Yaks as Revealed by Integrated Transcripts and Microbiome Analyses

Abstract: Growth retardation reduces the incomes of livestock farming. However, effective nutritional interventions to promote compensatory growth and the mechanisms involving digestive tract microbiomes and transcripts have yet to be elucidated. In this study, Qinghai plateau yaks, which frequently suffer from growth retardation due to malnutrition, were used as an experimental model. Young growth-retarded yaks were pastured (GRP), fed basal ration (GRB), fed basal ration addition cysteamine hydrochloride (CSH; GRBC) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 67 publications
14
34
0
Order By: Relevance
“…We also found that Rikenellaceae RC9 and Prevotella were abundant genera in all four fractions, in accordance with previous findings regarding ruminants generally (Henderson et al, ) and yaks (Hu et al, ; Xue et al, ; Zhang et al, ). Rikenellaceae RC9 can reportedly degrade structural carbohydrates and starch in the rumen of cows (Asma et al, ), while Prevotella spp.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also found that Rikenellaceae RC9 and Prevotella were abundant genera in all four fractions, in accordance with previous findings regarding ruminants generally (Henderson et al, ) and yaks (Hu et al, ; Xue et al, ; Zhang et al, ). Rikenellaceae RC9 can reportedly degrade structural carbohydrates and starch in the rumen of cows (Asma et al, ), while Prevotella spp.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that members of the phyla Bacteroidetes and Firmicutes were the dominant bacteria in the solid, liquid, and ventral epithelium fractions of yak rumen, in accordance with previous findings in ruminants generally (Henderson et al, ) and yaks specifically (Hu et al, ; Xue et al, ; Zhang et al, ; Zhou, Zhong, et al, ; Zhou, Fang, et al, ). These results indicate that the two phyla have adapted to wide ranges of gastrointestinal tract environments and play important roles in rumen ecology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further analysis using PCoA and Anosim showed that there was a significant difference between the cold and warm seasons, and the difference between the seasonal groups was significantly greater than that within the groups (P < 0.05). This may be due to the lack of food in the cold season, leading to a large difference in the acquisition of food resources (Sun et al, 2016), as seen in previous studies (Zeng et al, 2017;Zhou et al, 2017;Xue et al, 2018;Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…As a classic grazing livestock, the growth of yaks is directly affected by the natural environment. Because of the high altitude (more than 4000 m) of the Tibetan Plateau, there is only a cold season and a warm season [ 4 ]. The growth of animals is affected by the balance between the supply of food and the cost of survival each day [ 5 ].…”
Section: Introductionmentioning
confidence: 99%